MULTI-RELIGIOUS DIALOGUE, SOTERIOCENTRISM AND STUNTING: (A STUDY OF PAUL F. KNITTER'S THOUGHTS ON THE ISSUE OF STUNTING IN NTT) - Djami, Marla Marisa; Heydemans, Nency Aprilia; Boki, Lodiana; Nabunome, Mianti (Institut Agama Kristen Negeri Kupang, 2024)
Knitter proposes an approach or model of dialogue that is correlational and globally responsible between various religions, namely how religious communities seek to understand each other and talk on the basis of a shared commitment to the welfare of humanity and the environment. One of the social problems faced by religious communities in Indonesia, especially in NTT, is the problem of stunting. Not only the government, religions should also pay special attention. The aim of this research is to describe multi-religious dialogue and the concept of soteriocentrism according to religions in relation to the problem of stunting in NTT. This research was conducted using a qualitative research method with a phenomenological approach to see how the dialogue between religions touches the issue of stunting in NTT. Responsible dialogue between various religions as proposed by Knitter if implemented in NTT provides a strong foundation for promoting inter-religious cooperation, cross-cultural understanding, and concrete action for global human and environmental welfare, specifically in dealing with the problem of stunting in NTT. Religions are committed to working together in efforts to resolve this problem with a focus on education, empowerment and the active role of society. However, so far there has been no special program either from each religion or between religions regarding handling stunting in NTT. Stunting has not become a common basis for religions in building dialogue.